Loci and Natural Alleles for Low-Nitrogen-Induced Growth Response Revealed by the Genome-Wide Association Study Analysis in Rice (Oryza sativa L.) - Lv, Yang; Ma, Jie; Wang, Yueying; Wang, Quan; Lu, Xueli; Hu, Haitao; Qian, Qian; Guo, Longbiao; Shang, Lianguang (Frontiers in Plant Science, 2021)
Nitrogen is essential for plant growth and yield. It is therefore crucial to improve the nitrogen-use efficiency (NUE) of crop plants in fields. Here, we measured four major low-nitrogen-induced growth response (LNGR) agronomic traits (plant height, tiller number, chlorophyll content and leaf length) of a 225 rice natural population from the Rice 3K Sequenced Project across normal nitrogen (NN) and low nitrogen (LN) environments. The LNGR phenotypic difference between NN and LN levels was used to gene analysis using genome-wide association study (GWAS) combined with 111,205 SNPs from the available sequenced data of the 3K project. Totally 37 significantly-associated SNPs and 4 candidate genes for four LNGR traits were gained. Some loci collocated in the candidate regions, such as MYB61, OsOAT, and MOC2. To further study the role of candidate genes, we conducted haplotype analysis to identify the elite germplasms. Moreover, several other plausible candidate genes encoding LN-related or NUE proteins are worthy of mining. Our study provided novel insight into the genetic control of NUE, and further revealed some related novel haplotypes and potential genes in rice.